(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2015)
Cluster development of micro and small-scaled coffee industry is an effort to improve the economy of community by utilizing local resources. This study was aimed to identify phase of cluster growth through determinant factors of industrial cluster growth; to assess a linkage between economy players in the industrial cluster; and to identify strength, weakness, opportunity, and threat in coffee industry development. This research was carried out in Sumberwringin, Bondowoso District, East Java. Survey method through direct observation and interviews were conducted in this study. Data collected included primary and secondary data. Number of respondents were 25 industry players selected by judgement sampling method. The data were analyzed by exploratory descriptive with content analysis method. This research concluded that industrial cluster studied was still in phase of formation and initiative (embryo) and its growth pattern followed Pattern III. Interrelationship between core industries has not been established, while linkage between core industries and supporting industries had already well-established. Strength and opportunity in coffee industry development included raw materials availability, market segment growth. Small and micro enterprises credit facility, supporting facility, and labor availability. Constraints and threat faced by coffee industry included limited market access, in adequate machineries, limited working capital, raw materials quality, inconsistent product quality, credit claim, and competitors.